Expression of FGFR3 Protein and Gene Amplification in Urinary Bladder Lesions in Relation to Schistosomiasis - Hammam, Olfat; Aboushousha, Tarek; El-Hindawi, Ali; Khairy, Hosni; Khalil, Heba; Kamel, Amira; Akl, Maha; Abdel-Hady, Ahmed; Magdy, Mona; Badawy, Mohamed; El Kholy, Amr; Al Osili, Khalid; et al. (Open access Macedonian journal of medical sciences, 2017)
BACKGROUND: Bladder cancer represents the fifth most common malignancy worldwide and a major cause of cancer-related morbidity and death. Incidence and mortality rates have remained relatively constant over the past four decades. Urothelial bladder cancers have identified multiple risk factors.AIM: We aimed at evaluating the expression of the FGFR3 protein and gene amplification in the urothelial cells of neoplastic and non-neoplastic urothelial lesions of the urinary bladder, and correlation with tumour grade, stage and associated bilharziasis.MATERIAL AND METHODS: One hundred and five different urinary bladder lesions were studied, including 15 cystitis cases (9 bilharzial and 6 non-bilharzial cystitides), 75 urothelial carcinoma cases (18 bilharzial associated and 57 non-bilharzial associated) and 15 squamous cell carcinoma associated with bilharziasis, beside 5 control cases. Data concerning age, sex, tumour grade, stage, and associated bilharziasis were obtained. Each case was studied for FGFR3 expression, and FISH technique was applied on forty malignant cases that show high protein expression.RESULTS: The highest incidence of cystitis was in the fourth decade while of bladder cancer was in the seventh decade. Tumour grade was correlated significantly with tumour stage. FGFR3 correlates significantly with tumour grade, stage and with a bilharzial infestation. FGFR3 gene amplification was reported mainly in low grade and NNMBIC tumours.CONCLUSIONS: FGFR3 overexpression in malignant cases was significantly higher than in chronic cystitis. FGFR3 gene amplification was reported mainly in low grade and NNMBIC tumours. FGFR3 may be further studied as a subject for target therapy of bladder cancer.